Validação de questionários de avaliação da qualidade de vida em pacientes de psoríase Validation of life quality questionnaires for psoriasis patients - Gladys Aires Martins; Lucia Arruda; Aline Schaefer Buerger Mugnaini (Sociedade Brasileira de Dermatologia, 2004)
A psoríase é doença crônica que acomete entre 0,1 e 3% da população mundial e cujo impacto social e psicológico costuma ser subestimado.¹ Muitos estudos têm relatado o impacto produzido por essa doença na qualidade de vida dos pacientes, e questionários para analisar objetivamente essa incapacidade estão sendo descritos.1,2 É importante avaliar a percepção do portador de psoríase em relação a seu estado de saúde, incapacidade e qualidade de vida a fim de estabelecer a melhor terapêutica para cada indivíduo. Este artigo de EMC-D aborda a validação de dois questionários de avaliação da qualidade de vida para a língua portuguesa. Psoriasis is a chronic disease that affects about 0.1 to 3% of the world's population and most people underestimate the social and psychological impact of the disease.¹ MSeveral studies have described the many ways in which psoriasis affects patients' lives, and techniques have been described to quantify the disability caused.1,2 It is important to assess the perceived levels of health status, disability and quality of life when considering what kind of treatment options to offer patients with psoriasis. Underscoring the importance of this, the EMC-D article focuses on a validation of two quality of life questionnaires translated into Brazilian Portuguese.